The effect of marketing mix on purchase decision of fresh food on consumers in supermarkets system in Quy Nhon City - 1 (My University, 2018)
The effect of marketing mix on purchase decision of fresh food on consumers in supermarkets system in Quy Nhon City
Keywords: Marketing mix; Purchase decision; Fresh food